Sensitivity of western Canadian Pyrenophora teres f. teres and P. teres f. maculata isolates to propiconazole and pyraclostrobin. Issue 1 (2nd January 2017) - Akhavan, Alireza; Strelkov, Stephen E.; Askarian, Homa; Kher, Swaroop V.; Fraser, Michelle; Kutcher, H. Randy; Turkington, T. Kelly
Abstract: Pyrenophora teres f. teres ( Ptt ) and Pyrenophora teres f. maculata ( Ptm ), the causal agents of the net and spot forms of net blotch of barley, respectively, can be managed in western Canada with fungicides containing propiconazole and pyraclostrobin. Given the potential for development of fungicide resistance, the sensitivity of a collection of Ptt and Ptm isolates to propiconazole and pyraclostrobin was evaluated using microtitre plate bioassays. The concentration of propiconazole needed to inhibit fungal growth by 50% (EC50 ) was 1.5 mg L −1 for Ptt and 2.3 mg L −1 for Ptm, while the EC50 of pyraclostrobin was 0.015 mg L −1 for Ptt and 0.024 mg L −1 for Ptm . Subsequently, 39 Ptt and 27 Ptm isolates were screened with discriminatory doses of 5 mg propiconazole L −1 and 0.15 mg pyraclostrobin L −1 . Inhibition of growth as a result of propiconazole was 12–95% for Ptt and 48–92% for Ptm ; growth inhibition as a result of pyraclostrobin was 40–100% and 24–100%, respectively. Two Ptt isolates were insensitive to propiconazole, while one Ptm isolate was insensitive to pyraclostrobin. The latter also showed decreased sensitivity to propiconazole. The identification of net blotch isolates insensitive to these fungicides emphasizes the need for farmers to employ integrated crop management strategies to avoid fungicide resistance build-up.